Partisipasi Politik dan Perilaku Kekerasan di Indonesia Tinjauan Psikologi Politik - Buchory Muh Sukemi (Unisia, 2006)
Political participation as one of democratic state characteristics may be formed as election, lobbying, organization, connection, and violence behavior. Violence behavior is the form of political participation which frequency was rice since reformation era. With political psychology consideration, there are several theories explaining that violence behavior is influenced by (a) the model that was studies from experiences and observations (social study theory), (b) instinct that was brought since infant (instinct theory), (c)personal character (personality theory), (d) reciprocal interaction between personal factors (cognitive theory), and (e) frustration (aggressive-frustration theory). The political participation enhancement on reformation era, need to be managed with out violence behavior.